ChemInform Abstract: New Isolinariins C, D and E, Flavonoid Glycosides from Linaria japonica. Issue 36 (August 2016) - Widyowati, Retno; Sugimoto, Sachiko; Yamano, Yoshi; Sukardiman, Yoshi; Otsuka, Hideaki; Matsunami, Katsuyoshi
Abstract: Three new flavonoid glycosides, isolinariins C (Ia), D (Ib), and E (Ic) are isolated from the whole plant of Linaria japonica together with two known flavonoid glycosides and three known flavonoids.